HISTÓRIAS EM QUADRINHOS NA CONSTRUÇÃO DE UMA LITERACIA HISTÓRICA NOS LIVROS DIDÁTICOS PRESENTES NA CULTURA ESCOLAR - Oliveira, Geovane Gonçalves de (2019)
This dissertation presents an explanation about the Comics Books in the construction of a Historical Literacy in the textbooks present in the school culture, with this we define the general objective, which is to investigate the use of these Comic Books in the didactic books present in the school culture, we do this based on the theories of teachers Rüsen and Peter Lee.This work is in the field of Historical Education, and makes use of the authors who understand this field, to analyze the object of our research, then makes a contextualization about the school culture and the daily life that permeates the teacher-student and teacher relationship -material.After that the work enters into the empirical aspect of the project, working with the ideas of the textbooks, and how these are present inside the school, and how it happens its divugation, that is through governmental apparatus, being done this happens the analysis of the data collected in the field, fitting page snippets in three categories, Comic Books as a historical source, which would be comics produced in some historical period and problematized within the textbooks, Comic Books as a complement to the historical narrative of the textbook, which are those that complement the content , talk to the text, and finally, the category of Comics as an illustration, which are the stories that are simply in the book, without a more direct problem.